Growth mechanism of octahedron-like BaMoO4 microcrystals processed in microwave-hydrothermal: Experimental observations and computational modeling - Cavalcante, Laecio Santos; Sczancoski, Julio Cesar; Tranquilin, Rircado Luis; Varela, José Arana [UNESP]; Longo, Elson [UNESP]; Orlandi, Marcelo Ornaghi [UNESP] (Elsevier B.V., 2009)
Octahedron-like BaMoO4 microcrystals were synthesized by the co-precipitation method at room temperature and processed in microwave-hydrothermal at 413 K for different times (from 30 min to 5 h). These microcrystals were analyzed by X-ray diffraction (XRD), field-emission gun scanning electron microscopy (FEG-SEM) and transmission electron microscopy (TEM). XRD patterns showed that this material presents a tetragonal structure without the presence of deleterious phases. FEG-SEM and TEM micrographs revealed that the BaMoO4 microcrystals present an octahedron-like morphology with agglomerate nature and poly-disperse particle size distribution. These micrographs also indicated that the microcrystals grow along the [001] direction. The observed crystallographic planes in these structures were modeled computationally and a crystal growth model was proposed in order to explain the morphological changes as a function of processing time. (C) 2009 Chinese Society of Particuology and Institute of Process Engineering, Chinese Academy of Sciences. Published by Elsevier B.V. All rights reserved.
Keywords: BaMoO4; Growth process; Microwave-hydrothermal; Supersaturated solution